Auditoría a los Estados Financieros del Gobierno Autónomo Descentralizado Parroquial Rural de Chuquiribamba, de la Ciudad de Loja, Periodo 2014 - Buri Caraguay, Juan Vicente (2016)
This thesis called Financial Audit Financial Statements of the Autonomous Government Decentralized Parish Rural Chuquiribamba, City of Loja, period 2014, the same as was done with the aim of presenting a contribution to officials of the entity for a successful and timely decision-making; on the management of financial, material and human resources. I must emphasize that the overall objective is fulfilled when performing financial audit the Autonomous Government Decentralized Rural Parish Chuquiribamba to correct the management of financial resources of the entity; It was necessary for compliance with the specific objectives as: Determine whether is complying with the law applicable to the institution and technical regulations; goal that was met by reviewing and comparing operations with laws, regulations and rules governing the activities of the entity; the internal control mechanisms employed were also evaluated by the institution for the control, management and protection of public resources and thus take steps to correct the deficiencies of the implemented internal control, implementing internal control questionnaires for each of the components under examination certificates and preparing narratives of the deficiencies found; the reasonableness of balances presented in the financial statements prepared by the accountant was also verified the institution, by applying audit procedures set forth in analytical and 6 summary bonds; to determine the balances of the financial statements with statements comparing major and integrated general journal; also it revised if financial transactions executed by the institution have the documentation for support to make payments to its suppliers of goods and / or services, conducting analytical veracity and legality of transactions reviewing the documentation supporting these expenses, and finally submit to end of the period under review an audit report containing comments conclusions and recommendations, same that summarizes all the information that is exposed in the working papers and presents itself as a synthesis for knowledge and consideration of the officials of the entity. The methodology used in the financial audit; the use of techniques such as observation to know the reality in the entity, the guide previous visit for institutional information was applied was necessary, the application of the three phases of audit, whose methodology begins with preliminary planning in was made which knowledge of the entity, in the specific planning, evaluation of internal controls, programs and audit procedures, the evaluation matrix and audit risk rating for each component was made; He was then carried out the execution, using the procedures in audit programs and compliance through substantive finding evidence that the findings are supported with appropriate evidence and backs of the working papers; and in the communication phase of results, which is considered as the final part of the financial audit it is to the consideration of officials of the entity findings 7 and recommendations for better performance of their activities. The most important conclusion we have reached is that the entity has not been subject to any audit by the Comptroller General, therefore its officials do not know whether activities and financial operations are being developed under the rules governing the actions of the institution to fulfill corporate objectives for the benefit of society.